The Role of Profitability in Assessing The Financial Health of Islamic Banks - Dina Febrianti .P; Reski Ros Cahayana (Prosperia: Journal of Economic Development, Accounting, and Global Markets, 2026)
This inquiry establishes a comprehensive conceptual framework validating the structural role of profitability as an active diagnostic instrument in determining the microprudential stability of Sharia compliant financial institutions. Operating within an integrated systematic literature review design, the analytical architecture synthesizes macro level global industry standards with micro level sovereign statutory directives to trace the transmission pathways of institutional earnings. The qualitative data reduction reveals that fundamental rentability metrics including return on assets, return on equity, and net operating margins transcend basic accounting records to actively dictate the broader composite health classifications of modern banking corporations. Through meticulous thematic synthesis and conceptual triangulation, the findings demonstrate that sustainable profit generation directly strengthens operational resilience by accelerating organic capital retention, optimizing risk profile structures, and fortifying corporate governance efficiency. Ultimately, long term organizational survival requires a well integrated revenue optimization strategy that balances prudent asset liability management with aggressive digital banking transformations. Maintaining this structural equilibrium remains highly essential for securing public depositor trust and preserving systemic stability across competitive market landscapes.